Роль та місце інтелектуального потенціалу в розвитку промислових підприємств - Марчук, Леся Сергіївна (ФОП Шейніна О. В., 2020)
Обґрунтовано, що інтелектуальний потенціал на макроекономічному рівні в економічних глобалізаційних процесах виступає в ролі головного чинника, що визначає місце країни на світовій економічній арені. Експериментально підтверджено перевагу інтелектуалізації економіки та визнано її новим джерелом для сучасного суспільства. Це пояснюється тим, що інтелектуальні активи витісняють матеріальні, аналогічно, як інформація витісняє поточні активи. Розглянутий інтелектуальний потенціал може застосовуватися до ринку електроенергетики.

In today's conditions, the growth of the competitive environment and globalization processes significantly affect the state of the world economy, its development is determined by the level of use of intellectual potential. The most important and significant process is the intellectualization not only of the economy but also of production, which in turn is responsible for the high qualification of staff and continuous improvement. It is substantiated that the intellectual potential at the macroeconomic level in economic globalization processes acts as the main factor determining the country's place in the world economic arena. The advantage of intellectualization of the economy has been experimentally confirmed and recognized as a new source for modern society. This is because intellectual assets displace tangible ones, just as information displaces current assets. The considered intellectual potential can be applied to the electricity market.
The role and place of intellectual potential in the development of industrial enterprises
Keywords: інтелектуалізація економіки; конкурентоспроможність; фінансові потоки; інтелектуальна активність людини; intellectual potential; intellectualization of the economy; industrial enterprises; competitiveness; financial flows